Role and Challenges of International Organizations in Promoting Inclusive Education in India - Manjunath, B. S. (2015)
Salamanca Statement in 1994 laid the foundation for including children with special needs in regular schools. Mushrooming non-governmental organizations and parents of children with special needs started asserting their rights in India, resulted drafting progressive legislations like Persons with Disabilities Equal Opportunities Full Participation Act 1995 gave voice to the inclusion movement in India. In the recent past, United Progressive Alliance Government passing the Right to Education (RTE), ratifying legally binding United Nations Convention on Rights of Persons with Disabilities Document are few noteworthy milestones. Inclusive Education Movement in India stands for inclusion of socially economically disadvantaged and children with special needs. Post independence various constitutional and policy provisions to empower them. This paper hopes to throw ligh on India government's response in promoting inclusive education and challenges. This paper is a qualitative analysis and has also utilized secondary empirical data wherever necessary. This paper tries to provide a historical outline of Indian scenario and challenges. This paper has been divided into five chapters which include a brief overview of inclusion of children with special needs, review of literature followed by the role of international organizations. Resumo A Declaração de Salamanca de 1994 estabeleceu as bases para incluir crianças com necessidades especiais em escolas regulares. A proliferação de organizações não-governamentais e os pais de crianças com necessidades especiais começaram a reivindicar os seus direitos na Índia, resultando em legislações progressistas como a Lei de Participação Total de Pessoas com Deficiência de 1995, que deu voz ao movimento de inclusão na Índia. No passado recente, o United Progressive Alliance Government (Governo da Aliança Progressista Unida), a aprovação do Direito à Educação (RTE) e a ratificação do documento juridicamente vinculante da Convenção das Nações Unidas sobre os Direitos das Pessoas com Deficiência são alguns marcos notáveis. O Movimento de Educação Inclusiva na Índia traduz-se na inclusão de crianças socialmente e economicamente desfavorecidas e crianças com necessidades especiais. Este artigo procura lançar uma luz sobre a resposta do governo da Índia na promoção de educação inclusiva e os seus desafios. Este artigo utiliza uma análise qualitativa e também dados empíricos secundários sempre que necessário e tenta fornecer um esboço histórico do cenário e dos desafios indianos. Este artigo foi dividido em cinco capítulos que incluem uma breve visão geral da inclusão de crianças com necessidades especiais, revisão da literatura seguida do papel das organizações internacionais.